(Manaã) : canoa pantaneira do Rio Paraguai : manifestação cultural na comunidade Potreiro, Cáceres, Pantanal Mato-Grossense - Victoriano, Celso Ferreira da Cruz (2006)
This research aims at investigating the knowledge of the fisherman from Pantanal in terms of the construction of the canoe in a dialogic environmental perspective projecting the local needs and knowledge in order to promote the Math and Environmental Education. The following of the constructive steps of the canoe in Pantanal, in Cáceres Mato Grosso, is the central theme of this research. The context of the study is São Bento farm, called “Potreiro” nearby Vila Aparecida District, old Bezerro Branco which is located 50 km far from Cáceres, in the Road 343 Cáceres to Barra dos Bugres in Mato Grosso, far 800 m from the Paraguay River. Qualitative descriptive research of ethnographic type. It was used for the data survey: bibliographical and field research through the participating observation; open interview with an iconographic record and tape recordings. It was registered that in order to build a canoe the hand maker uses the trunk of the tree called Chimbuva (Enterolobium contortisiliquum (Vell.) Morong – Mimosaceae), it is measured by vines where it was cut and the spaces for the benches, the localization of the prow and the stern and also of the equilibrium point through the logical math’s reasoning. In this research we have also considered the construction process of the canoe paddle using an interpretative analysis observing the steps to build up the canoe. The data presented here evoke, from a math point of view as also from an environmental conservation point of view, care with the conservation and preservation of the cultural knowledge.